Transformasi Asesmen Formatif melalui Teknologi Metaverse, Studi Mixed-Methods dalam Pendidikan Kejuruan di Indonesia - Heriyanto; Heni Jusuf (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
The increasing integration of advanced technology in education has created new opportunities to enhance teaching practices. However, evaluation systems still dominated by traditional methods have not been able to fully represent students' applicative competencies. This study explores the implementation of metaverse technology, specifically through the use of FrameVR, in formative assessment at the Vocational High School (SMK) level in Indonesia. A mixed-methods approach was employed, combining quantitative survey data from 38 students with qualitative interviews to evaluate the impact on student motivation, collaboration, and engagement. The findings indicate a significant positive impact of the metaverse-based assessment environment on student participation and interest. Students reported higher motivation and stronger collaboration skills when completing tasks within the immersive virtual environment. This research highlights the potential of metaverse platforms to transform traditional assessment into an interactive, engaging, and skills-oriented experience, aligning with the demands of the modern workforce. Implications for future research and educational policy are discussed, particularly concerning infrastructure, digital equity, and teacher readiness in adopting immersive learning technologies. The successful implementation of the metaverse in education is highly dependent on infrastructural preparedness, financial support, enhancement of teacher competencies through training, and robust data security and privacy guarantees.